INTERAKSI DAN KEMAMPUAN AWAL SISWA DALAM PEMBELAJARAN THINK-PAIR-SHARE BERBANTUAN KARTU PLUSMINUS TERHADAP PENINGKATAN PEMAHAMAN KONSEP MATEMATIS SISWA - Lili Nur Indah Sari (REKOGNISI : Jurnal Pendidikan dan Kependidikan, 2018)
The background of this research was the students’ less in understanding mathematical concepts. The teacher didn’t use media in thaeching learning proses about addition and subtraction of integer. Based on teachers’ statement, thewe were for about 50% students got lower score under KKM (minimum mastery criteria). The objectives of this research was to know whether the interaction between students’ prior ability and their learning toward improvement ability in understanding mathematical concepts. This research used quasi-experimental method. Based on data analysis, the result showed that the students who were given think pair share with plusminus card got higher score than students who were not. The calculation of their score were F value on learning factors (PKT and PKB) of 4.249 with a significance of 0.001 smaller than the significance level of 0.05, so that H0 is rejected.It can be concluded that there is no interaction between students’ learning and students’ prior ability into their improvement in understanding mathematical concepts. It was proved from the result calculation 0,919 more than significance value 0,05.